Maszynopisy powielone Publikationsstelle des Preussischen Geheimen Staatsarchivs z zasobów Institut für Oberschlesische Landesforschung w zbiorach Biblioteki Śląskiej w Katowicach (PDF 718 KB) (Książnica Śląska, 2025)
The author presents the book collection of the Institut für Oberschlesische Landesforschung, transferred to the Biblioteka Śląska after WorldWar II by the Zbiornica Księgozbiorów Zabezpieczonych in Katowice.It consists of over three hundred duplicated typescripts, published bythe Publikationsstelle des Preußischen Geheimen Staatsarchivs. Theseare scientific publications in the field of social sciences, economicsand geography translated into German.